Deep brain stimulation macroelectrodes compared to multiple microelectrodes in rat hippocampus - Arcot Desai, Sharanya; Gutekunst, Claire-Anne; Potter, Steve M.; Gross, Robert E. (Frontiers in Neuroengineering, 2014)
Microelectrode arrays (wire diameter < 50 µm) were compared to traditional macroelectrodes for Deep Brain Stimulation (DBS). Understanding the neuronal activation volume may help solve some of the mysteries associated with DBS i.e., its mechanisms of action. We used C-fos immunohistochemistry to investigate neuronal activation in the rat hippocampus caused by multi-micro- and macroelectrode stimulation. At ±1 V stimulation at 25 Hz, microelectrodes (33 µm diameter) had a radius of activation of 100 µm, which is 50% of that seen with 150 µm diameter macroelectrode stimulation. Macroelectrodes activated about 5.8 times more neurons than a single microelectrode, but displaced ~20 times more neural tissue. The sphere of influence of stimulating electrodes can be significantly increased by reducing their impedance. By ultrasonic electroplating (sonicoplating) the microelectrodes with platinum to increase their surface area and reduce their impedance by an order of magnitude, the radius of activation increased by 50 µm and more than twice the number of neurons were activated within this increased radius compared to unplated microelectrodes. We suggest that a new approach to DBS, one that uses multiple high-surface area microelectrodes, may be more therapeutically effective due to increased neuronal activation.